Epigenetic clock as a correlate of anxiety - Marečková, Klára; Pačínková, Anna; Klasnja, Anja; Shin, Jean; Andrýsková, Lenka; Stano-Kozubík, Kateřina; Pausová, Zdenka; Brázdil, Milan; Paus, Tomáš (NeuroImage. Clinical, 2020)
DNA methylation changes consistently throughout life and age-dependent alterations in DNA methylation can be used to estimate one's epigenetic age. Post-mortem studies revealed higher epigenetic age in brains of patients with major depressive disorder, as compared with controls. Since MDD is highly correlated with anxiety, we hypothesized that symptoms of anxiety, as well as lower volume of grey matter (GM) in depression-related cortical regions, will be associated with faster epigenetic clock in a community-based sample of young adults. Participants included 88 young adults (53% men; 23-24 years of age) from the European Longitudinal Study of Pregnancy and Childhood (ELSPAC) who participated in its neuroimaging follow-up and provided saliva samples for epigenetic analysis. Epigenetic age was calculated according to Horvath (Horvath, 2013). Women had slower epigenetic clock than men (Cohen's d = 0.48). In women (but not men), slower epigenetic clock was associated with less symptoms of anxiety. In the brain, women (but not men) with slower epigenetic clock had greater GM volume in the cerebral cortex (brain size-corrected; R2 = 0.07). Lobe-specific analyses showed that in women (but not men), slower epigenetic clock was associated with greater GM volume in frontal lobe (R2 = 0.16), and that GM volume in frontal lobe mediated the relationship between the speed of epigenetic clock and anxiety trait (ab = 0.15, SE = 0.15, 95% CI [0.007; 0.369]). These findings were not replicated, however, in a community-based sample of adolescents (n = 129; 49% men; 12-19 years of age), possibly due to the different method of tissue collection (blood vs. saliva) or additional sources of variability in the cohort of adolescents (puberty stages, socioeconomic status, prenatal exposure to maternal smoking during pregnancy).
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Pregnancy; Epigenesis, Genetic; Humans; Longitudinal Studies; úzkost; dítě; Child; Depressive Disorder, Major; Female; Gray matter volume; mladý dospělý; Sex differences; lidé; Anxiety; Anxiety Disorders; epigeneze genetická; depresivní porucha unipolární; Gray Matter; ženské pohlaví; longitudinální studie; DNA methylation age; Male; Adolescent; úzkostné poruchy; těhotenství; šedá hmota; Young Adult; mužské pohlaví; Frontal lobe; mladiství